The Role of Investment Zakat Consumption and Economic Growth in Sustainable SDG Realization - Widawati, Yesi; Putri, Tasya Berliana; Ainafaid, Deviani; Setyowati, Eni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: This study aims to determine the impact of zakat, investment, and consumption on economic growth, with the ultimate goal of achieving sustainable SDGs. The research focuses on zakat variables as a means to bolster Indonesia's economic growth, consumption, and investment. It emphasizes the importance of synergizing these factors to enhance economic growth and welfare, including poverty alleviation, wealth redistribution, and increased employment opportunities. Methodology: The research methodology involves economic data analysis, a comprehensive literature review, and the utilization of the Ordinary Least Squares (OLS) model. This model is used to explore and unveil how zakat, investment, and consumption collectively influence economic growth. Results: States that zakat and consumption variables have a positive and significant impact on economic growth. Indicates that the investment variable does not affect economic growth. Applications/Originality/Value: Emphasizes the necessity of the government's role in considering zakat instruments while creating regulations to boost economic growth, particularly in poverty alleviation and fair distribution of income and consumption. Urges the government to seek increased investment in the country to stimulate job availability, aligning with the SDGs' goal of "no poverty".